The Networked Electorate: The Internet and the Quiet Democratic Revolution in Malaysia and Singapore - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2009)
This paper is intended to be a contribution to the literature on claims of the democratising effect of the Internet. The paper begins by setting out the arguments and also critiques of claims of the democratising power of the Internet. In order to test the validity of these arguments, the author will undertake a comparative study of the impact of the Internet on recent general elections in Malaysia and Singapore. The study will demonstrate that in the case of Singapore, the Internet has merely exerted some pressure on the pre-existing laws and state-imposed norms governing free speech; in contrast, in Malaysia, the Internet was a major contributory factor to what has been described as a 'political tsunami' during the recent general election. In this comparative study, the author will attempt to explain why the impact of the Internet has been so different in both jurisdictions which share similar laws, culture and language. It will be suggested that, in spite of their similarities, the main reasons for this phenomenon are subtle but important differences in terms of legal, social, economic conditions and also the political climate in both jurisdictions. Despite this difference, the claim made in this paper is that the Internet, due to its evolving architecture, is beginning to generate important norms governing free expression which are capable of having an effect on the electorate. In both countries, the Internet connects individuals to become networks which in turn create powerful echo chambers which have or will ultimately strain the effectiveness of pre-existing laws and state-imposed norms governing free speech. It is also suggested that the recent events in Malaysia has inspired nascent Internet activism in Singapore which potentially may be of greater influence in future elections.